Analisis Penerimaan Followers tentang Klarifikasi Vina Muliana pada Akun Tiktok @Vmuliana dalam konten “Cerita Perjalanan Karierku” - Afifi, Luluk; Amalia, Diana (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2024)
This study aims to find out the Acceptance of Followers to Vina Muliana's clarification on the Tiktok account @VMuliana in the content "My Career Journey Story", with a qualitative descriptive study. to explain the depth of the phenomenon by collecting data in detail and depth. This research uses a qualitative approach. The researcher focused on the research subject, namely Followers @VMuliana which was taken by 9 @VMuliana followers who would be used as informants. The researcher conducted an in-depth interview by contacting via WhatsApp phone. Interviews via WhatsApp can be done in various ways, namely by doing text messages, voice notes and video calls. Based on the results of the research described above, the conclusions that can be drawn: 1. Vina Muliana's clarification is still maintaining the good name of the insider, the insider route is the right and fast solution, entering with the insider route must still follow the procedures that have been set by the company such as the on-boarding process, brobation and periodic assessments. It can be categorized into the Dominant-Hegemonic Code category. 2. Another opinion related to the acceptance of Vina Muliana's clarification is that it causes unfair competition, lowers credibility and social jealousy between workers. However, they do not support the clarification content from Vina Muliana contained on the Tiktok account @VMuliana the theme "My Career Journey Story", this can be categorized into the Opposition Code category. 3. There was no Negotiated Code category because in this clarification of Vina Muliana, the informants only accepted and rejected the Clarification on the basis of their respective points of view